2021
DOI: 10.1002/chem.202100171
|View full text |Cite
|
Sign up to set email alerts
|

Catechol‐Coordinated Framework Film‐based Micro‐Supercapacitors with AC Line Filtering Performance

Abstract: Coordination polymer frameworks (CPFs) have broad applications due to their excellent features, including stable structure, intrinsic porosity, and others. However, preparation of thin‐film CPFs for energy storage and conversion remains a challenge because of poor compatibility between conductive substrates and CPFs and crucial conditions for thin‐film preparation. In this work, a CPF film was prepared by the coordination of the anisotropic four‐armed ligand and CuII at the liquid–liquid interface. Such film‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In addition, the power density and energy density of COE‐4‐based MSC were measured. The maximum power density and energy density reached to 2.16 and 0.93 μWh cm −2 , which is better than that of reported materials, such as graphene, [ 34 ] d‐Ti 3 C 2 T x , [ 35 ] PANI nanowires, [ 36 ] EG, [ 37 ] Cu‐DTHAB, [ 31 ] etc. (Figure 4f).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, the power density and energy density of COE‐4‐based MSC were measured. The maximum power density and energy density reached to 2.16 and 0.93 μWh cm −2 , which is better than that of reported materials, such as graphene, [ 34 ] d‐Ti 3 C 2 T x , [ 35 ] PANI nanowires, [ 36 ] EG, [ 37 ] Cu‐DTHAB, [ 31 ] etc. (Figure 4f).…”
Section: Resultsmentioning
confidence: 71%
“…Such high areal-specific capacitance outperforms most reported conductive polymer-based MSCs (Table S2, Supporting Information). [26][27][28][29][30][31] Then, the double-layer capacitor (C dl ) and pseudocapacitance (C p ) contributions were studied via Trasatti's approach. [32] Figure S26, Supporting Information, shows the reciprocal of the area capacitance versus the square root of the scan rate, the curve of the area capacitance and the reciprocal of the square root of the scan rate.…”
Section: Resultsmentioning
confidence: 99%
“…In 2010, Miller et al first demonstrated the ECs capable of line filtering at 120 Hz using the vertically oriented graphene nanosheets (VOGN) grown directly on current collectors. 8 Since then, a wide variety of the nanostructured EC electrodes including carbon-based materials, 2,3,6,9-28 metal oxides, [29][30][31] chalcogenides, [32][33][34][35] nitride, 36 MXene, 37 and polymers 2,22,35,[38][39][40][41] have been investigated for fast response at high frequencies, with carbon-based receiving the most attention.…”
Section: Introductionmentioning
confidence: 99%
“…The capacitance contribution rate of PAE-NiNiPcF 8 from C p and C dl were calculated to be 49.5% and 50.5% using the Trasatti method, respectively, which quantitatively analyzes the C dl behavior of PAE-NiNiPcF 8 . [40] In order to check the energy storage performance of PAE-NiNiPcF 8 -CST, the electrochemical behavior was investigated by electrochemical CV and GCD in PVA/H 2 SO 4 (Figure S49, Supporting Information). The integral area of CV curve for PAE-NiNiPcF 8 -CST-based MSC exhibits excellent specific C v of 27.8 F cm −3 at scan rate of 2 mV s −1 , which is comparable to PAE-NiNiPcF 8 (28.1 F cm −3 at scan rate of 2 mV s −1 , Figure S49a, Supporting Information).…”
Section: Pae-m 1 M 2 Pcf 8 As Electrodes For Mscsmentioning
confidence: 99%